Acceptability Model of The Use of Forest Area Policy in Bangka Belitung - Setiawan, Dian; Nurrochmat, Dodik Ridho; Kuncahyo, Budi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
The use of forest area (UFA) policy is a forest management policy by government to accommodate the needs for mining sector in forest area.This study aims to analyze the factors that become key drivers and influence the acceptance of UFA program and also build the agent-based modelsimulation of UFA policy. The method built in this research is using Structural Equation Modelling and Agent-Based Modelling approach. Based onthe results of confirmatory factor analysis, the factors that play a role in the acceptance of the program is the understanding and participation ofstakeholders related to UFA program and the availability of land allocation to be given license to borrow forest area. In addition, based on the ABMapproach, in order to anticipate the increased deforestation rate in available forest cover, it is necessary to accelerate and increase the rate ofmining reclamation activities by license holders.Keywords: agent-based modelling, structural equation modelling, the use of forest area